Sarcoma de Ewing/ tumor neuroectodérmico primitivo de la fosa nasal - Aliaga, Rolig (2019)
A 30 year-old patient with recurrent epistaxis for two years, then noted a left nasal tumor, visual disturbance and nasal obstruction on the same side. The histopathology study reveals an expansive process of small round blue cells in the left nostril; and, the immunohistochemistry concluded as an Ewing's sarcoma/primary neuroectodermic tumor. It was carried out a left posterior medial maxillectomy, chemotherapy and local radiotherapy.